Geo-environments of the Abobral Pantanal, Mato Grosso do Sul, Brazil - de Queiroz, Roberta Franco Pereira; Corrêa, Guilherme Resende; Gradella, Frederico dos Santos; Bernardes, Gabriel Miranda Paranaíba; Reynaud Schaefer, Carlos Ernesto Gonçalves; Ruivo, Maria de Lourdes Pinheiro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The Pantanal basin is seasonally flooded, forming distinct landscape units or geo-environments. The Abobral Pantanal is one of the Pantanal sub-regions. This study aimed to report soil physic-chemical characteristics and evaluate soil-plant relations. We subdivided the landscape using hydromorphism, phytophysiognomies, relief, and soil conditions. In the Cordilheira geo-environment, a non-flooded area, the occurrence of snail shells buried in the soil was noted, inducing occurrence of Chernozems. This geo-environment showed higher levels of organic Carbon and available Phosphorus. The Petrocalcium horizon at Cordilheira contributes to vegetation deciduousness and to stability against erosion processes. In the seasonally flooded geo-environments, Lagoa Intermitente, Campo com Cambará, and Corixo, Planosols occur generally, which supports the maintenance of a higher water table due to a planic B horizon with vertic characteristics.